EVALUASI PELAKSANAAN PROGRAM BANTUAN OPERASIONAL SEKOLAH DI SEKOLAH DASAR NEGERI NO. 125549 KELURAHAN MARTOBA KECAMATAN SIANTAR UTARA PEMATANGSIANTAR - MUSTIKA W SASTIA HUTASUHUT (Welfare StatE, 2013)
Fuel price increases in recent years it is feared will reduce the purchasing power of the poor. It can hamper efforts completion Compulsory Basic Education Program Nine Years, because the poor will be increasingly difficult to meet the cost of education. In order to address the impact of rising fuel prices, the government has largely reallocate its budget to the four programs, namely education, health, rural infrastructure, and direct cash subsidy. One of the programs in the field of education is the School Operational Assistance provides assistance to schools with the goal of free education for students who can not afford, and ease the burden for the other students in order to support the achievement of program Compulsory Nine-Year Basic Education. Through this program, the government provides funding to the schools at the primary and junior high schools to help reduce the burden of education costs to be borne by the parents. Type of research is descriptive, where the population numbered 247 people. In this case the sample is 34. The sampling technique used in this study were stratified proportional random sample. The sampling technique is implemented in a state where the population is made ​​up of groups have multilevel arrangement. Data collection techniques used are literature studies and field studies consisting of distributing questionnaires (questionnaire), interview and observation. The data analysis technique used is descriptive quantitative by collecting, managing, presenting and describing the results of research. The results of the data analysis it can be seen that the School Operational Assistance Program at Elementary School No.. 125 549 Martoba Village district of North Siantar Pematangsiantar going well. In this case the BOS program greatly help ease the burden of families towards the cost of education, so it helps keluaraga poor or unable to properly weave education o support the achievement of the compulsory nine-year basic education and this program is very useful for various stakeholders, including students and parents. Keywords: Evaluation, School Operational Assistance, Poor Students